QANAT FISHES IN MARKAZI AND SIRJAN BASINS OF KERMAN PROVINCE, IRAN - M. Ebrahimi (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2008)
A survey on the qanat fishes of the Markazi and Sirjan basins of Iran was carried out in the year 2001. Using electroshocker, cast net and river seine, we collected 767 specimens from73 qanats in the study area. We also measured pH, water temperature, air temperature, oxygen and other important attributes of the environment. The fish specimens belonged to 2 orders, 3 families and 3 species. Of the order Cypriniformes, the family Cyprinidae was present with one species Capoeta damascina (Valenciennes, 1849) and the family Balitoridae was represented with one species Nemachilus sargadensis (Nikolskii, 1900). Of the order Cyprinodontiformes, the family Poecilidae was represented with the species Gambusia affinis (Baird & Girard, 1853)